ACCOUNTABILITY, TRANSPARENCY, AND EFFECTIVENESS ON ORGANIZATIONAL PERFORMANCE OF REGIONAL INCOME MANAGEMENT AGENCY - Ibnu Zaenal Arifin; Erdiriyo; Ellin Herlina (Journal Of Resource Management, Economics And Business, 2022)
effectiveness on the organizational performance of the Regional Revenue Management Agency of Cirebon Regency. Research Methodology: This research was conducted at the Regional Revenue Management Agency office of Cirebon Regency. This research is included in the category of causal associative research using a quantitative approach. With the number of respondents as many as 74 employees with saturated sampling technique means that all the population is used as a sample in the study. Sources of data used are questionnaires, observation and documentation techniques. The data analysis techniques are instrument test (validity test and reliability test), percentage descriptive analysis, classical assumption test, and multiple regression analysis and hypothesis testing using SPSS for Windows version 24.0. Results: The results showed that the three independent variables had a very positive effect on the dependent variable. This is shown from the results of tcount of all variables greater than ttable 1,994. In addition, from the results of jointly testing the hypothesis, the value of F_count > F_table is 2.735. And the value of R Square shows the number 0.700 which means that (X1), (X2), and (X3) have an influence of 70.0% on organizational performance (Y). The remaining 30.0% is influenced by other variables not examined. And from the R value, it can be seen that there is a very strong relationship between the three independent variables on the dependent variable in this study. Limitations: Limited number of research samples and research variables. Contribution: Theoretical contributions to accountability, transparency, and effectiveness and organizational performance. Practical contribution to regional income management agency.